2012
DOI: 10.1111/j.1365-2672.2012.05432.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages are synergistic with bacterial interference for the prevention ofPseudomonas aeruginosabiofilm formation on urinary catheters

Abstract: Aims We hypothesized that pretreating urinary catheters with benign Escherichia coli HU2117 plus an anti-pseudomonal bacteriophage (ΦE2005-A) would prevent P. aeruginosa biofilm formation on catheters – a pivotal event in the pathogenesis of catheter-associated urinary tract infection (CAUTI). Methods and Results Silicone catheter segments were exposed to one of four pretreatments (sterile media; E. coli alone; phage alone; E. coli plus phage), inoculated with P. aeruginosa, then incubated up to 72 hours in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 26 publications
0
41
0
2
Order By: Relevance
“…As part of the resurrection of phage research in Western countries to solve the problem of increases in antibiotic resistance (4,48), bacteriophages which lyse host bacteria have aroused increasing interest for their potential application as antibiofilm agents (4,(8)(9)(10)(11)(12). Also, quorum quenching has been investigated as a biofilm control approach in many clinical (49,50) and industrial (23,24,51) settings, due to the essential role of quorum sensing in regulating biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of the resurrection of phage research in Western countries to solve the problem of increases in antibiotic resistance (4,48), bacteriophages which lyse host bacteria have aroused increasing interest for their potential application as antibiofilm agents (4,(8)(9)(10)(11)(12). Also, quorum quenching has been investigated as a biofilm control approach in many clinical (49,50) and industrial (23,24,51) settings, due to the essential role of quorum sensing in regulating biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
“…Phages are capable of lysing host bacteria in experimental single-and mixed-species bacterial biofilms (6,7). Phages have been explored as antibiofilm agents in diverse industrial and clinical settings, including phage therapy (4), biofilm-infected medical devices (8)(9)(10)(11), and filtration membranes (12). In many biofilm systems, however, EPS still pose a challenge, limiting the bactericidal effect of phages (13,14).…”
mentioning
confidence: 99%
“…The investigators observed that the blanket of bacteria and phage across the catheter surface prevented P. aeruginosa adherence [34], suggesting a potential therapeutic probiotic/ phage approach to prevent CAUTI.…”
Section: Urinary Tract Microcosmmentioning
confidence: 99%
“…Antagonistic mechanisms include: production of factors that kill or inhibit the growth of neighbors, production of chemical signals that can interfere with or disrupt the behavior or physiology of neighbors, or hoarding of nutrients that starves neighbors [15,[30][31][32][33]. 'Surface blanketing' occurs when one species occupies all the attachment sites on a surface, thereby preventing the attachment of another [15,34,35]. Investigating antagonistic relationships between microbes not only provides insight into bacterial social behavior, but also may hold keys to disrupting biofilm structure and composition, potentially leading to novel treatments for biofilm-related infections.…”
mentioning
confidence: 99%
“…Thus, it should be put in consideration that for treating biofilms temporary by phages, it would be required that the biofilm cells surface be exposed to some disruption prior to phage application. Other combinations are also possible exactly like in the case of biological systems Liao et al [69]; noticed that combining phages with commensal bacteria had synergistic effects in preventing biofilm formation on silicone catheter segments while Zhang and Hu [70]; observed when using phages coupled with biocide like (chlorine) the effects on filters is increased. However, further studies have to target on exploring phage activity in the multispecies context, animal models, and in conjunction with other antimicrobials [71].…”
Section: Combining Phage With Other Agentsmentioning
confidence: 99%